2019
DOI: 10.1111/jcmm.14890
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic imaging using hyperpolarized 13C‐pyruvate to assess sensitivity to the B‐Raf inhibitor vemurafenib in melanoma cells and xenografts

Abstract: Nearly all melanoma patients with a BRAF‐activating mutation will develop resistance after an initial clinical benefit from BRAF inhibition (BRAFi). The aim of this work is to evaluate whether metabolic imaging using hyperpolarized (HP) 13C pyruvate can serve as a metabolic marker of early response to BRAFi in melanoma, by exploiting the metabolic effects of BRAFi. Mice bearing human melanoma xenografts were treated with the BRAFi vemurafenib or vehicle. In vivo HP 13C magnetic resonance spectroscopy was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Altered cell metabolism is a key component of the downstream consequence of activating BRAF mutations in melanoma, 38 with evidence of reduced oxidative phosphorylation activity and increased glycolysis 39 . The data presented here are in agreement with the current hypotheses that indicate treatment with vemurafenib leads to a reduction of in vitro aerobic glycolysis and glucose consumption in BRAF‐mutant melanoma cells 22,23 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Altered cell metabolism is a key component of the downstream consequence of activating BRAF mutations in melanoma, 38 with evidence of reduced oxidative phosphorylation activity and increased glycolysis 39 . The data presented here are in agreement with the current hypotheses that indicate treatment with vemurafenib leads to a reduction of in vitro aerobic glycolysis and glucose consumption in BRAF‐mutant melanoma cells 22,23 …”
Section: Discussionsupporting
confidence: 87%
“…In the experimental protocol described here, deuterated solvation of HP [1‐ 13 C] pyruvate combined with a highly sensitive microcoil system with a micro‐reservoir in the vertical plane, provided a means of increasing the throughput of in vitro DNP‐MRS experiments. Traditional HP experiments using cell suspensions require more than 10 7 cells, 22–25 which utilizes excessive resources and incubator space. The microcoil system allows for reproducible measurements of k PL with ~10 5 cells.…”
Section: Discussionmentioning
confidence: 99%
“…BRAF is one of the genes upregulated in melanoma cells, and inhibition of BRAF signaling has been a top target for therapy. Metabolic consequences as a result of the inhibition of BRAF by vemurafenib have been investigated using HP [1- 13 C] pyruvate MRSI in melanoma cell lines [67][68][69]. One of the studies showed a reduction in pyruvate-to-lactate conversion in the BRAF mutant melanoma cell line compared to the vehicle control, whereas an increased pyruvate-to-lactate conversion was recorded in the BRAF wildtype melanoma cell line compared to vehicle control [67].…”
Section: Melanomamentioning
confidence: 99%
“…Hyperpolarized 13 C-NMR data were acquired, as previously described [26]. 1-13 C pyruvic acid (Sigma-Aldrich, Saint Louis, MO, USA) was mixed with 15 mM trityl radical OXO63 and doped with 2 mM gadolinium (Guerbet, Villepinte, France).…”
Section: Hyperpolarized 13 C-nmr Spectroscopy and Data Analysismentioning
confidence: 99%